Public information tools, socio-economic attributes, and environmental behavior concerning plastic carrying bags in Bangkok - Muslin Kunopasvorakul; Edsel E. Sajor; Ranjith Perera; Bernadette Resurreccion; Canada (CIDA) {u2013} RTG Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2010)
Today, global warming and reducing plastic bag use is the priority concern throughout the world, including Thailand. The campaign on reducing plastic bags is used as a symbol of the responsibility of the Thai government and Thai people in terms of global warming. For Thailand, the campaign{u2019} s first phase was started in May 2009 from the campaign in Bangkok. The cooperation received from various stakeholders both public and private sectors and through public relations campaigns via the media, both news and advertising inserts in various TV sho ws, radio programs as well. When May 2010, Bangkok Metropolitan Administration has collaborated with famous department stores in Bangkok, such as CP All 7 - 11, Tesco Lotus, and Big C to projects 21 THB per bag,3 reducing plastic bag usage in the Bangkok are a and will be used as a pilot project to bill laws and regulations on plastic bag use control in the future. This study shows the relationship of socio - economic factors of people and the use of public information tools that impact people behavior on using plastic bags. Socio - economic factors are correlated with the plastic bags practices. Each factor has different effects on people behavior. The variables will different affect people behavior on plastic bag use as different and/or similar practices between male and female, childhood and adolescent, adult and elderly, different education, as well as occupation and income groups. Moreover this study also found that public information tool is limited in terms of the implementation within specific situation. T hat will lead to non - achievement of implementing the tool, hence, a combination of such tool with other tools such as law and regulation measures and economic tools, including its use in the general situation will achieve even more. Finally, this study has identified alternative strategies that are possible in implementation with the BMA condition.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Urban Environmental management
Thesis (M.Sc.) - Asian Institute of Technology, 2010
Keywords: Plastic bag -- Environmental aspects -- Thailand -- Bangkok